ELECTROMAGNETIC PUSHKA MODEL TO CREATE RECOMMENDATIONS AND SUGGESTIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The thesis demonstrates model structure of the electromagnetic canon, it’s working process and physic procedures in it’s elements.